A Comparative Study on Optical Characteristics of InGaAsP QW Heterostructures of Type-I and Type-II Band Alignments - Garima Bhardwaj; Sandhya K.; Richa Dolia; M. Abu-Samak; Shalendra Kumar; P. A. Alvi (Institute of Advanced Engineering and Science, 2018)
In this paper, we have configured InGaAsP QW (quantum well) heterostructures of type-I and type-II band alignments and simulated their optical characteristics by solving 6 x 6 Kohn-Luttinger Hamiltonian Matrix. According to the simulation results, the InGaAsP QW heterostructure of type-I band alignment has been found to show peak optical gain (TE mode) of the order of 3600/cm at the transition wavelength 1.40 µm; while of type-II band alignment has achieved the peak gain (TE mode) of the order of 7800/cm at the wavelength of 1.85 µm (eye safe region). Thus, both of the heterostructures can be utilized in designing of opto-or photonic devices for the emission of radiations in NIR (near infrared region) but form the high gain point of view, the InGaAsP of type-II band alignment can be more preferred.